The Efforts To Increase Vegetative Growth of White Corn (Zea mays L) With Vesicle Arbuscular Mycorrhizae (VAM) and Distance Planting Treatment: Efforts To Increase Vegetative Growth of White Corn (Zea mays L) With Vesicle Arbuscular Mycorrhizae (VAM) and Distance Planting Treatment - Silitonga, Yusnita Wahyuni; Erwin Harahap, Darmadi; Hamidi Hasibuan, Ilal; Hanafiah Nasution, Muhammad Nizar (Jurnal Online Pertanian Tropik, 2022)
The purpose of this study was to see the effect of giving Vesicle Arbuscular Mycorrhizae (VAM) on the vegetative growth of white corn (Zea mays L), distance treatment of plant and interaction both of them on the vegetative growth of white corn. This study used a randomized block design (RBD) on factorial with two-factor and three replications. The first factor is the treatment of giving VAM (A) with various doses consisting of A1 (10 g/plot), A2 (20 g/plot) and A3 (30 g/plot), while the second factor is the treatment of plant spacing (J) with various sizes consisting of J1 (50 cm x 15 cm), J2 (50 cm x 25 cm) and J3 (50 cm x 35 cm). Data collection starts from planting to flowering, namely plant height, number of leaves, flowering time. Data analysis was carried out through analysis of variance and further test of DMRT at 95% confidence level. Based on the results of the study, it was found that the fungal treatment only had a significant effect on plant height and cob length, but did not significantly affect the number of leaves, flowering time. The plant spacing treatment only had a significant effect on plant height but had no significant effect on the number of leaves and flowering time. The interaction of the fungus treatment and plant spacing treatment showed that there was an interaction effect of the two treatments on plant height but did not significantly affect the number of leaves, flowering time. The treatment interaction A3J3 had the highest plant size of 114.55 cm.